URGENSI PELAYANAN ADMINISTRASI KEPENDUDUKAN MELALUI UPT DISDUKCAPIL DI KECAMATAN AMARASI BARAT KABUPATEN KUPANG - , Ignasius L. Wangge; Urbanus Ola (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Public services are crucial in the governance framework. One of the most important services is population administration services. This research is conducted to examine the significance of population administration services provided by the government, provincial local governments, and district/city governments for the community, so that the process of population administration services should be carried out in the best possible way to meet the needs and satisfaction of the community regarding government services. In addition, population administration services in Kupang Regency have been implemented at the sub-district level through the Baun UPT Disdukcapil. However, based on data collected in February 2023, many people still do not have population documents. Therefore, this research aims to describe the urgency of population administration services through the Baun UPT Disdukcapil in the West Amarasi Sub-district, Kupang Regency. This research uses a qualitative descriptive method. The speed and accuracy of processing population registration services and civil registration services are carried out in accordance with the applicable standards for population administration services at the Population and Civil Registration Office of Kupang Regency.